Assessing the Utility of an Electronic Research Database to Capture Whole Systems Practice at Two Naturopathic Outpatient Teaching Clinics. (July 2013) - Leung, Brenda M. Y.; Flower, Gillian; Cooley, Kieran; Habib, Chris; Gowan, Matt; Podgrabinski, Stefan; Seely, Dugald
This observation study assessed the utility of an electronic Naturopathic Patient Database at 2 naturopathic teaching clinics as a research and educational tool. Focusing on the whole systems practice of naturopathic medicine using individualized treatment protocols, patients from the Canadian College of Naturopathic Medicine outpatient teaching clinic and the Boucher Institute of Naturopathic Medicine outpatient teaching clinic were assessed. Data were collected on patient demographics, laboratory values, physical measures, treatment protocols, and validated questionnaires. Results showed the Naturopathic Patient Database was able to capture both standardized and individualized measures of care for research purposes. A number of substudies were generated by student interns using the database. Limitations identified included limited resources for training faculty, interns, and administrators on program use and data entry; also, data quality and completeness were problematic. However, the Naturopathic Patient Database captured data on the individualized nature of naturopathic care and had the ability to collect and compare large amounts of data.